2015
DOI: 10.1155/2015/106537
|View full text |Cite
|
Sign up to set email alerts
|

An eHealth System for Pressure Ulcer Risk Assessment Based on Accelerometer and Pressure Data

Abstract: Pressure ulcers are a common skin disease which is associated with pain, reduced autonomy, social isolation, and reduced quality of life. There are several systems for monitoring of pressure ulcer-related risk factors on the market, but up to now no satisfactory solution is available, especially for people with medium pressure ulcer risk. We present a novel pressure ulcer risk assessment and prevention system, which combines the advantages of accelerometer and pressure sensors for monitoring pressure ulcer ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The results of the study showed a weak correlation between the eHealth system and the paper-based Braden scale in predicting pressure injury risk (correlation factor = 0.31). 22 Another study that developed an Android-based application is the research conducted by Kim (2016), who developed an Android-based application aimed at detecting pressure injury risk. The study was conducted as a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed a weak correlation between the eHealth system and the paper-based Braden scale in predicting pressure injury risk (correlation factor = 0.31). 22 Another study that developed an Android-based application is the research conducted by Kim (2016), who developed an Android-based application aimed at detecting pressure injury risk. The study was conducted as a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Seguindo a mesma linha de raciocínio, Hayn e colaboradores (21) , mostra que no seu estudo de posicionamento de sensores em colchões com o auxílio de acelerômetros (dispositivo que mede a vibração ou a aceleração do movimento de uma estrutura) para detec-…”
Section: Fatores Extrínsecosunclassified
“…Another example is provided in [10], where a wearable wireless monitor continuously measures the duration and orientation of the posture of the patient through an accelerometer built into the torso and adaptive posture algorithms accurately measure the angle of the spine vertebral in order to classify the orientation of the patient. Other approaches in [14] for the PUs prevention focus more on detecting long-term pressure to particular skin regions of the body. All these systems use pressure sensors because pressure is one of the main important factors for the development of PUs.…”
Section: Related Workmentioning
confidence: 99%
“…The total risk for each person to develop PUs can be estimated in accordance with different scales: one of these is the Braden scale, which is based on several risk factors, such as poor motion activity, but also temperature, skin humidity and malnutrition [14]. PUs negatively affect the quality of life of patients and prolong their recovery process thus increasing the costs for the healthcare systems.…”
mentioning
confidence: 99%